School and Students: Encounters and Disagreements in Relation with Knowledge - Soledad Vercellino; Nora Liliana Tarruella; Romina Alejandra van den Heuvel; Rocío Belén Andrade; Mariana Andrea Guerreiro; Cristina Irigoyen; Lidia Mónica Cardinale (Universidad Nacional, Costa Rica, 2017)
The following article presents some preliminary results of a study conducted under the research project "The constitution of the relation with knowledge in students of the last cycle of primary education and the first one of secondary level" (National University of Comahue, Department of Psychopedagogy, 2015), implemented by the Department of Psychopedagogy at the Regional Center Atlantic Area, National University of Comahue, Argentina. In continuity with studies of human sciences that address the relation with knowledge of the subjects, and following Charlot's (2008) theoretical contributions, this study aimed to analyze the secondary processes of establishing the relation of students with knowledge, focusing on students who culminate the primary education and start secondary level in public schools in Rio Negro Province. Identifying and problematizing specifically the meanings these students give to school knowledge, and more generally, to school and their past and future trajectories in it. The research methodology was qualitative, hermeneutical and interpretative. We implemented a psycho-pedagogical accompanying workshop; it consisted in various meetings carried out during school hours, each one organized around a particular problem and linked to a production activity- sought, to recover the students' discourse. On the basis of written, oral, graphic and dramatic productions, we researched the objects of knowledge, the activities the students mastered, and the relational forms acquired. As a result, we found that students reported different figures of learning (Charlot, 2008),giving special relevance to the ways of relating. In turn, from school, the apprehension of knowledge is emphasized but as knowledge-relational object. Regarding the know-writing, writing follows different rules to those proposed at school that we might call standard. Finally, when you refer to the places where they learn, even though they mention different spaces to school and family, these two spaces continue to be privileged sites and institutions for learning.